M 31 novae M31N 2012-06a and M31N 2014-02a detected in X-rays with XMM-Newton - Henze, M.; Sturm, R.; Ness, J. -U.; Greiner, J.; Della Valle, M.; Sala, G.; Hernanz, M.; Shafter, A. W.; Hornoch, K.; Orio, M.; Hartmann, D. H.; Kaur, A.; et al. (2014)
We report the detection of two M 31 novae as supersoft X-ray sources (SSS) in a recent XMM-Newton target of opportunity (ToO) observation. The 24 ks observation was obtained on 2014-08-09.89 UT to study the SSS emission of nova M31N 2014-02a, previously detected by Swift (ATel #6374).
Keywords: Nova; Transient